Improving postnatal social support using antenatal group-based psychoeducation: a cluster randomized controlled trial - Tessema, Marta; Abera, Muluemebet; Birhanu, Zewdie (Frontiers in Global Women's Health, 2025)
BackgroundInadequate social support is the predominant cause of postnatal depression, which needs to be promoted through interventions. The objective of this study was to investigate the effect of antenatal group-based psychoeducation on improving postnatal social support.MethodsThe trial design was a cluster randomized controlled trial. The study was conducted on 32 non-adjusted health centers (clusters) among 550 pregnant women. Using simple randomization, health centers were randomized into 16 intervention and 16 control groups. The intervention group received both standard prenatal care and group-based psychoeducation sessions, whereas the control group received standard prenatal care alone. The study included all pregnant women who were between 12 and 20 weeks gestation and had a Patient Health Questionnaire-9 <10 level of depression. We used a functional social support questionnaire in a face-to-face interview to assess social support at 12–20 weeks of gestation and 6 weeks postpartum. An intention-to-treat analysis was done. We used relative risk and a mixed-effects multilevel logistic regression for data analysis.ResultOut of 550 enrolled pregnant women, end-line data were collected from 511 participants, with an overall end-line response rate of 92.9%. Statistical analysis revealed that the intervention resulted in a substantial difference in all dimensions of social support between arms, although no difference was detected at baseline. As compared to that in controls, the total postnatal social support in the intervention clusters was considerably higher [190 (66.4%) vs. 88 (33.3%)], P = 0.001). Mothers who were under the intervention arms and received antenatal group-based psychoeducation were 2.04 times more likely to have postnatal social support (RR = 2.044, 95% CI: 1.684–2.481) compared to those who were under the control arms and received the usual care. Finally, mixed-effect analysis indicates that after adjusting for individual and community-level variables, the final model shows the intervention increased the total social support by 3.61 (AOR = 3.61, 95% CI: 2.14–6.09).ConclusionThe implementation of antenatal group-based psychoeducation intervention resulted in a statistically significant effect in improving postnatal social support. This intervention approach must therefore be implemented and promoted in maternal healthcare services. Clinical Trial Registrationhttps://pactr.samrc.ac.za/, identifier (PACTR 202203616584913).